Informatization Measurement Scale: Methods and Tools for Assessing the Level of Digital Maturity - Tomczak, Dawid (Journal of Positive Management, 2025)
Abstract: Purpose: The purpose is to identify methods and tools for assessing organizations’ digital maturity. Methodology/approach: This publication presents the most effective methods of determining the level of informatization, such as the Digital Technology Readiness Assessment – Questionnaire, TOGAF® Standard, as well as reveals real-world examples of how to use the questionnaire based on the research sample of 220 respondents. Findings: Nowadays, in rapidly changing business environments, informatization is a key factor determining organizations’ competitiveness. Measuring the level of digitization and informatization is fundamental for businesses to identify areas that require improvements and assess digital maturity. Keywords: informatization, digitalization, informatization measurement scale, digital maturity model Paper type: Research paper